2014
DOI: 10.1001/jamaophthalmol.2013.7682
|View full text |Cite
|
Sign up to set email alerts
|

Eye Care Availability and Access Among Individuals With Diabetes, Diabetic Retinopathy, or Age-Related Macular Degeneration

Abstract: IMPORTANCE Understanding whether differences in the local availability of eye care professionals are related to differences in realized access to eye care is important for assessing whether and where public health efforts are needed to increase access to eye care professionals.OBJECTIVE To examine whether the county-level availability of ophthalmologists and optometrists is associated with measures of realized access to eye care for individuals with diabetes mellitus, diabetic retinopathy, or age-related macul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…This is consistent with national data showing that minorities tend to have lower rates of screening [10]. Screening rates also vary by geographic location, with rural populations having lower rates of screening, likely due to issues with access to care [11]. Diabetes patients with retinopathy who have access to reti- nopathy screening at or near the office of their primary care provider may more likely be screened out of convenience compared with those who are referred to an eye care specialist [12].…”
Section: Disparitiessupporting
confidence: 88%
“…This is consistent with national data showing that minorities tend to have lower rates of screening [10]. Screening rates also vary by geographic location, with rural populations having lower rates of screening, likely due to issues with access to care [11]. Diabetes patients with retinopathy who have access to reti- nopathy screening at or near the office of their primary care provider may more likely be screened out of convenience compared with those who are referred to an eye care specialist [12].…”
Section: Disparitiessupporting
confidence: 88%
“…Previous research on the US found that greater county-level availability of ophthalmologists, with availability measured using population-weighted quartiles of the county-level number of ophthalmologists per capita, was associated with increased use of eye care services and better visual health outcomes (Gibson, 2014). These findings motivate the decision to describe eye care provider availability in a similar fashion in this paper.…”
Section: Measurement Of the County-level Availability Of Eye Care Promentioning
confidence: 74%
“…On average, counties with lower eye care provider availability per capita had fewer physicians per capita, lower population density, and a poorer, less urban, and older population than counties with greater eye care provider availability per capita. These characteristics may exacerbate or moderate the challenges for public health interventions in counties with limited eye care provider availability, although most of these characteristics increase the expected challenge (Gohdes et al, 2005;Layde et al, 2012;Prevent Blindness America and National Association of Chronic Disease Directors, 2005;Prevent Blindness America, 2004;Saadine et al, 2003;US Centers for Disease Control, 2009;Zhang et al, 2007). For example, older individuals are both more likely to need eye care services and to use eye care services (US Centers for Disease Control, 2009;Lee et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations